KEBIJAKAN POLITIK KOLONIAL BELANDA DAN JEPANG TERHADAP PENDIDIKAN ISLAM DI INDONESIA - Hendra Julianto; Faridi (STKIP Subang, 2026)
Islamic education in Indonesia underwent significant changes due to the intervention of Dutch and Japanese colonial powers, which, according to educational colonialism theory, should have weakened its institutional existence, yet in reality demonstrated remarkable resilience. This study aims to comparatively analyze the political policies of Dutch and Japanese colonial rule toward Islamic education, as well as to reveal the survival strategies and cultural resistance of Islamic educational institutions amid the pressures of both regimes. The research employed a library research method, examining various literature sources such as scientific journals and relevant prior studies, with data analyzed qualitatively-descriptively through identification, comparison, and synthesis across sources. The results show that the Dutch implemented a repressive approach through regulations such as the Teacher Ordinance and the Wild School Ordinance, which restricted the operations of pesantren and madrasahs, while Japan displayed a superficial leniency that remained oriented toward wartime propaganda interests. Despite facing different structural pressures, Islamic educational institutions managed to survive through networks of ulama, community solidarity, and curriculum flexibility, thereby functioning as both educational institutions and bases of cultural resistance and collective Muslim identity. These findings are relevant to the formulation of fairer and more inclusive education policies, in line with the achievement of SDG 4.